(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Calming traffic is one of the main approaches to ensuring safety in city streets and it is based on the concept of speed containment. The aim of this approach is to minimize passing transit flows through the streets of district importance, to ensure the pedestrians and cyclists safety, as well as the impact on the behavior of drivers in urban conditions. City streets should be designed taking into account the restriction of "extra" speed, as well as in accordance with the category and purpose. It is necessary to take into account the functionality of the street, the uniformity of the traffic flow, the appropriateness of the imposed limitations, the predictability of the technical means used to organize traffic.